Thermoplastische Hybridlaminate mit variabler Metallkomponente. Issue 6 (June 2014) - Nestler, D.; Jung, H.; Arnold, S.; Wielage, B.; Nendel, S.; Kroll, L.
<x xml:space="preserve">Abstract</x> Hybrid laminates combine the positive properties of the metal and fibre reinforced plastic (FRP) components. Advantages of the FRP, like formability, recyclability as well as suitability for mass production, provide an outstanding advantage over thermosetting matrices. For the production of the hybrid laminates, at first continuous fibers and thermoplastic films are pre‐consolidated to fibre‐reinforced unidirectional tapes. Subsequently, these are pressed together with the metal component in a loadcapable optimized arrangement. Thereby the interface between the FRP and the metal foils is of crucial importance. This paper focuses on hybrid laminates with carbon‐fiber reinforced polyamide (CF‐PA6) functioning as core layers and glass‐fiber reinforced polyamide (GF‐PA6) as intermediate layers between the centre and metal component. Laminates in 2/1 and 3/2 structure with two respectively three metal layers and one respectively two FRP layers are examined. For the metal foil, the aluminium alloy EN AW‐6082 and the titanium alloy Ti3Al2.5V (Grade 9) are used. The production of these laminates, development and adjustment of the interface and the evaluation of mechanical properties are investigated in this article.